Early corneal wound healing and inflammatory responses after SMILE : comparison of the effects of different refractive corrections and surgical experiences - Liu, Yu-Chi (2018)
To investigate the early corneal wound healing and inflammatory responses after small incision lenticule extraction (SMILE) with different power of corrections and surgical experiences using a rabbit model.Twenty-four rabbits underwent SMILE with -2.00, -4.00, and -8.00 diopters (D) correction. One eye of each rabbit was operated on by surgeon 1 (experienced) and the contralateral eye was operated on by surgeon 2 (novice). Slit-lamp examination, anterior segment optical coherence tomography (AS-OCT), and in vivo confocal microscopy were performed at 1 day and 1 week postoperatively. The corneas were harvested for immunofluorescence of markers for inflammation (CD11b), wound healing (fibronectin), and keratocyte response (HSP47).All corneas appeared clear throughout the follow-up period. In vivo confocal microscopy showed a greater reflectivity after -8.00 D than -2.00 D correction at day 1 at the lenticule anterior, posterior, and extracted lenticule planes (surgeon 1: P = .004, .041, and .038; surgeon 2: P = .012, .045, and .031). Different refractive corrections did not significantly affect the expression of CD11b, fibronectin, and HSP47. In the -2.00 D group, eyes operated on by surgeon 2 had thicker central corneal thickness evaluated by AS-OCT (P = .049) and exhibited more CD11b- and HSP47-positive cells at day 1 at the small vertical incision (P = .039 and .042).The early inflammatory and wound healing responses after SMILE were minimal. In the early postoperative period, less surgical experience resulted in an increased inflammatory response in low myopic corrections. Greater keratocyte response was seen in high myopic corrections irrespective of surgeon experience.